Bescheidung, Unterscheidung, Entscheidung. Zur Philosophie als Weisheit in Schellings “Einleitung in die Philosophie der Offenbarung” - Jonas Francesco Erulo (Aisthema: International Journal, 2016)
In the distinction of a negative and positive philosophy - which occurs within philosophy itself - and the definition of their mutual relation, philosophy in itself is at stake in its nature and its meaning. In order to correspond to the claim of freedom - which is at the beginning of philosophising - a philosophy is required that is able to "engage the great objects", a philosophy "that does not only skirt these by formulas", a philosophy that "can match life" and is "far from being limited to the sad work of mere negation and destruction taking its power from reality". Thus, according to etymology, philosophy is defined as "wisdom", as quest of freedom for its sense. On the other side, Schelling applies that "there is no wisdom for man as long as there is none in the objective course of things […]. I want wisdom means: I want an existence posed through wisdom, foresight and freedom". Positive philosophy deals with the free and thus not apriorily anticipable principle of being (or: existence) and to being (or: existence)  as contingently posed.